All-in-one bipolar electrode: A new concept for compact and efficient water electrolyzers. (December 2021) - Yang, Gaoqiang; Xie, Zhiqiang; Yu, Shule; Li, Kui; Li, Yifan; Ding, Lei; Wang, Weitian; Zhang, Feng-Yuan
Abstract: Highly compact and efficient proton exchange membrane electrolyzer cells (PEMECs) are strongly desired for commercializing hydrogen production. Here, a novel concept of all-in-one bipolar electrode (AIOBE) is proposed for high-efficiency and compact PEMECs with the help of 3D printing and sputtering coating. AIOBE ideally integrated catalyst layer (CL)/gas diffusion layer/bipolar plate/current distributor/gasket, which significantly reduced component quantity on the cathode side of PEMECs from 5 to 1, cut down on part weight and volume, and drastically accelerated the fabrication and maintenance processes. Moreover, AIOBE with the micro-scale flat surface and nano-scale rough CL provided an ultralow ohmic resistance (~ 100 mOhm cm 2 ) and a high catalyst utilization. Finally, AIOBE delivered a practical voltage of 1.62 V and a high energy efficiency of 91% at 1000 mA/cm 2, and its mass activity (4.48 A/mgPt ) was 14 times higher than conventional PEMECs. This work provides a new route for developing highly compact electrochemical devices, such as fuel cells, electrolyzers for N2 reduction and CO2 conversion, and many more. Graphical Abstract: ga1 Highlights: All-in-one bipolar electrode is fabricated using 3D printing and sputtering coating. 5 components in water electrolyzer are combined into 1 multifunctional part. A high catalyst mass activity of 4.48 A/mgpt is achieved. Interfacial ohmic resistance at cathode side is eliminated. All-in-one bipolar electrode enables the highly compact water electrolyzer.